Umiejętności społeczno-emocjonalne w uczeniu się jako procesie poznawania siebie i świata - Barabasz, Grażyna (Studia Edukacyjne, 2021)
The author discusses the Concept of Multidimensional Skills (for education) presented in the Report of the World Bank Learning to realize education`s promise (2018), with particular emphasis on its first part - socio-emotional skills. Socio-emotional skills are the basic competences for learning, for getting to know oneself, for developing awareness of oneself and the social world, and for building social relationships. The author analyzes the learning process in various contexts.